Identification of Science Process Skills Students of Junior High School Batang Hari Jambi In Science Lessons - Wirayuda, Ricky Purnama; Fitriani, Riska; Wibisono, Gunawan; Afifah, Nisaul (IJIS Edu : Indonesian Journal of Integrated Science Education, 2022)
The purpose of the research conducted by the researcher was to find out how the description of students' science process skills in science subjects at SMPN 6 Batang Hari Jambi Regency. The method used in this research is a descriptive method with a qualitative approach. This research was conducted in Batang Hari Regency, precisely at SMPN 6 Batang Hari. The subjects of this research were 134 students of class VIII. The instruments used in this study are: (1) Observation sheets, (2) open interviews. The results of observations and interviews show that the achievement of students' science process skills is still low, in general, which is related to teaching and learning activities carried out. This is due to several factors, including: Students are not required to be active in exploring their own knowledge in the learning process. The physics learning process rarely uses investigation and experiment activities. Learning activities carried out are mostly lectures by teachers to students